2021
DOI: 10.3390/ani11061595
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Bird Species Literacy—Activity/Interest and Specialization Are More Important Than Socio-Demographic Variables

Abstract: Biodiversity is declining, and knowledge about biodiversity declines in a similar way. Previous studies have already addressed predictors of species knowledge. Here, we studied bird species knowledge related to demographics, but also to individual differences in affinity to nature, by including (i) birding specialization and (ii) bird-related activities/interest. Data were collected from July to October 2020 via an online questionnaire, containing demographic data, birding specialization, interest/activity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…Numerous studies have addressed the factor structure of the birding specialization questionnaires and the measurement model used here seems well established (Lee and Scott, 2004). Furthermore, Randler and Heil (2021) showed that people who assessed their bird knowledge higher in the questionnaire similarly performed better in a subsequent cognitive test where they had to identify different bird species (r = 0.7). This adds to the quality of the questionnaire.…”
Section: Discussionmentioning
confidence: 84%
“…Numerous studies have addressed the factor structure of the birding specialization questionnaires and the measurement model used here seems well established (Lee and Scott, 2004). Furthermore, Randler and Heil (2021) showed that people who assessed their bird knowledge higher in the questionnaire similarly performed better in a subsequent cognitive test where they had to identify different bird species (r = 0.7). This adds to the quality of the questionnaire.…”
Section: Discussionmentioning
confidence: 84%
“…Concerning the parameters tested in our survey, species knowledge increases with age. In almost all other studies, age was also a significant predictor of species knowledge [ 38 ], but species knowledge does not simply increase with life experience; it also decreases when comparing age cohorts of different times. In the year 2007, German pupils scored 15% more points on a same-species identification test than they did in a follow-up study a decade later [ 20 , 21 ], for multiple possible reasons.…”
Section: Discussionmentioning
confidence: 99%
“…This disconnection seems to have only a small influence on bird species knowledge as other surveys observed even slightly better bird species knowledge in the group of urban citizens [ 21 ] or no significant influence of the hometown’s number of inhabitants at all [ 19 , 20 ]. Another study found hometown sizes not relevant, but a distance >10 km to the next forest patch was correlated with a lower identification score [ 38 ]. Although we did not test the species knowledge of different indigenous groups, our results might support the presumption that members of post-industrial societies have less knowledge of nature than members of indigenous communities [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The question of estimated bird species richness at the respective place was based on a categorical scale containing nine categories (0–5; 6–10; 11–20; 21–30; 31–40; 41–50; 51–60; 61–70; over 70 species present; scale adapted after Ferraro, et al [ 34 ] and Southon, et al [ 35 ]). We also asked about birding specialization based on how many bird species participants can recognize by appearance without help from books or apps [ 36 ]. In addition, some demographic variables were asked for: age in years, gender (male, female, diverse), and graduation (university degree, coded dichotomous “yes or no” with “yes” meaning at least a bachelor’s degree).…”
Section: Measurements and Methodsmentioning
confidence: 99%
“…As demographic effects may have an influence on bird species knowledge [ 36 ], we analyzed the estimated species richness with respect to age, gender, self-reported birding skill level, and university degree.…”
Section: Measurements and Methodsmentioning
confidence: 99%